2022
DOI: 10.1039/d2cc04247a
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically activated dual-locked fluorescent probes to monitor H2S-induced DNA damage

Abstract: NAN0-N3 and NAN6-N3 could monitor DNA damage induced by the overexpression of H2S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This suggests that they have self-protection strategies that researchers have not fully recognized. Previous studies have shown that H 2 S stimulates the production of reactive oxygen species (ROS) and decreases glutathione levels in bacteria, resulting in lipid peroxidation and DNA damage, , and this inhibitory effect could not be relieved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that they have self-protection strategies that researchers have not fully recognized. Previous studies have shown that H 2 S stimulates the production of reactive oxygen species (ROS) and decreases glutathione levels in bacteria, resulting in lipid peroxidation and DNA damage, , and this inhibitory effect could not be relieved.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, H 2 S can activate the bacterial oxidative response, protect cells from oxidative damage, and increase resistance to antibiotics . On the other hand, H 2 S at high concentrations seriously stimulates reactive oxygen species (ROS) production and inhibits microbial activity after long-term exposure . When H 2 S is produced in large amounts, it is often accompanied by bacterial disintegration, death, and decay of the whole consortia …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures were solved using direct methods and refined with fullmatrix least-squares on F 2 using the SHELX-2018 program package. 31 In compound 2, Cd(5) co-occupies the same site with Co(5), while Cd(6) co-occupies the same site with Co (6). We validated the empirical formulae with results from elemental analysis, thermogravimetric analysis, energy-dispersive spectroscopy analysis and X-ray photoelectron spectroscopy analysis (Fig.…”
Section: X-ray Crystallographic Studymentioning
confidence: 95%
“…In recent years, metal-oxo-cluster based compounds with unique molecular structures have been widely studied due to their potential applications in magnetism, catalysis, biomedicine, proton conduction, etc. [1][2][3][4][5][6][7][8][9][10] The Sb(III) ion with an ns 2 configuration has stereochemically active lone pair electrons in the s orbitals, making it important in many optoelectronic fields such as ferroelectricity and nonlinear optics. 11,12 The Sb (III) ion can interact with the O 2− ion in various coordination modes, such as [SbO 3 ], [SbO 4 ], and [SbO 5 ], which can further combine with other metal ions to form heterometallic oxocluster based compounds in various structural types.…”
Section: Introductionmentioning
confidence: 99%